In vitro differentiation of human embryonic stem cells into ovarian follicle-like cells - Dajung Jung (Nature Portfolio, 2017)
In vitro production of human oocytes for the treatment of female infertility is a goal in reproductive medicine. Here, the authors establish in vitroconditions to generate human ovarian follicle-like cells from human embryonic stem cells.